2011
DOI: 10.1016/j.juro.2011.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Outlet Obstruction Induced Expression of Prostaglandin E 2 Receptor Subtype EP4 in the Rat Bladder: A Possible Counteractive Mechanism Against Detrusor Overactivity

Abstract: Activation of the EP4 receptors expressed in bladders with outlet obstruction may suppress detrusor muscle contraction and afferent activity. This might be a compensatory mechanism to counteract the deterioration of storage function in bladders with outlet obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Lower urinary tract symptoms (LUTS) are commonly seen in males with benign prostatic hyperplasia (BPH), and storage LUTS such as urinary frequency and urgency overlap with those of overactive bladder. BPH-induced bladder outlet obstruction (BOO) has been proposed as a mechanism inducing enhanced bladder afferent activity and storage LUTS due to various factors including decreased release of nitric oxide (Kim et al 2011), increased release of prostaglandin E2 from the urothelium (Beppu et al 2011), decreased potassium channel activity (Aydin et al 2012), or ischaemia and oxidative stress to the detrusor (Lin et al 2008). However, the size of prostate and LUTS severity do not always correlate and patients sometimes suffer LUTS even in the absence of prostate enlargement, which suggests that multiple factors contribute to the pathogenesis of LUTS (Funahashi et al 2011;Chung et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) are commonly seen in males with benign prostatic hyperplasia (BPH), and storage LUTS such as urinary frequency and urgency overlap with those of overactive bladder. BPH-induced bladder outlet obstruction (BOO) has been proposed as a mechanism inducing enhanced bladder afferent activity and storage LUTS due to various factors including decreased release of nitric oxide (Kim et al 2011), increased release of prostaglandin E2 from the urothelium (Beppu et al 2011), decreased potassium channel activity (Aydin et al 2012), or ischaemia and oxidative stress to the detrusor (Lin et al 2008). However, the size of prostate and LUTS severity do not always correlate and patients sometimes suffer LUTS even in the absence of prostate enlargement, which suggests that multiple factors contribute to the pathogenesis of LUTS (Funahashi et al 2011;Chung et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LH binds to the LH receptor and activates the cyclic adenosine monophosphate/protein kinase A pathway and the phospholipase/inositol phosphate signaling pathways in human uterine smooth muscle cell . These pathways increase cyclooxygenase and the production of PGE2, which induces relaxation of the urethra in the lower urinary tract in humans, suggesting that increasing the PGE2 concentration could lead to urinary incontinence. In the rat urethra, PGE2 is thought to relax smooth muscle and decrease urethral pressure .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the excitatory effect of PGE 2 on bladder function is inhibited by an EP1 antagonist in rats and is suppressed in EP3 receptor knockout mice . Concerning the role of EP4 receptor, one study reported that an EP4 receptor antagonist attenuated bladder activity in rats with overactive bladder induced by cyclophosphamide, whereas another reported that an EP4 receptor agonist suppressed bladder activity in rats with bladder outlet obstruction . Further studies are required to elucidate the mechanisms underlying EP4 receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…20 Concerning the role of EP4 receptor, one study reported that an EP4 receptor antagonist attenuated bladder activity in rats with overactive bladder induced by cyclophosphamide, 21 whereas another reported that an EP4 receptor agonist suppressed bladder activity in rats with bladder outlet obstruction. 22 Further studies are required to elucidate the mechanisms underlying EP4 receptor signaling. Regarding involvement of EP2 receptor in the bladder, a couple of reports have suggested that EP2 receptors might be expressed in guinea pig bladders.…”
Section: Discussionmentioning
confidence: 99%